Cardiopulmonary Bypass Time During Surgery for Acute Type A Aortic Dissection and Mid-Term Survival - Uimonen, Mikko (Switzerland, 2025)
We evaluated the association between cardiopulmonary bypass (CPB) time during surgery for acute type A aortic dissection (ATAAD) and mid-term survival. Data of 1122 patients who underwent surgery for ATAAD in eight Nordic centers from January 2005 to December 2014 were retrospectively analyzed. An adjusted logistic regression analysis was performed to investigate the association of incremental 30 min CPB time on 30-day mortality. In addition, the patients were divided into those that underwent surgery with >210 min (n = 369) or <210 min CPB time (n = 605) based on spline analysis and a receiver operating characteristic curve. The restricted mean survival time ratios adjusted for patient characteristics and surgical details between the groups were calculated for survival and aortic reoperation-free survival. The median follow-up time was 2.6 (inter-quartile range 0.9–4.9) years. Incremental CPB time was associated with higher 30-day mortality (OR 1.25 per 30 min, 95% CI 1.15–1.35, p < 0.001). Mid-term survival for all patients was inferior in the >210 min group as compared with the <210 min group (adjusted restricted mean survival time ratio 0.88, 95% confidence interval [CI] 0.81–0.96, p = 0.003). Reoperation-free survival was similar in patients with CPB time > 210 min as compared with <210 min. Prolonged CPB time is associated with higher 30-day mortality and inferior mid-term survival but not with inferior reoperation-free survival after surgical repair of ATAAD.